BEIS Biomass Feedstocks Innovation Programme Phase 1 : Automated planting, weeding and harvesting of Miscanthus in harsh environments, exploiting complementary microalgal production for increased revenue options : Final Report.: Automated planting, weeding and harvesting of Miscanthus in harsh environments, exploiting complementary microalgal production for increased revenue options : Final Report. (2022) - Unknown
No abstract available